(untitled) (Research, Society and Development, 2022)
To report the experience on teaching-learning and the use of active methodologies of the thematic unit basic care for women’s health in the Nursing course from the perspective of monitors. This is an account of the experience of students in the teaching-learning and monitoring of women’s health in the pregnancy, puerperal and climacteric cycle, of the Bachelor of Nursing course of a University Center, located in Agreste Pernambucano. The experience took place between the months of August and December 2021, in which 05 teachers, 29 students, participated in the activities. The first stage of the teaching process was based on the theoretical basis in the teaching-learning of women’s health, followed by the second stage, with the construction of practical skills in the thematic unit. The teaching strategies and resources used in the classes were dialogued expository classes, conversation circles, group debates and laboratory practices. It is considered that the teaching-learning process should be based on methodologies that stimulate creativity, criticality and students’ autonomy in the construction of skills and competences. The monitoring practice allows student-monitors to improve their knowledge and practices on the subject, also allowing them to develop important skills in the area of teaching, in addition to sharing their previous experiences with students.